2009
DOI: 10.1021/ma900756w
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Nanofibrous Film Doped with a Conjugated Polymer for DNT Fluorescence Sensor

Abstract: Electrospun nanofibrous film doped with a fluorescent conjugated polymer P was developed as a sensory device for detection of the explosive 2,4-dinitrotoluene (DNT). Polymer P obtained through a Sonogashira cross-coupling polymerization showed high affinity and excellent fluorescence quenching property toward electro-deficient compound DNT in solution. A versatile and effective electrospinning technique, which effectively reduced aggregation and fluorescence self-quenching of the conjugated polymers in thin fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 34 publications
5
98
0
2
Order By: Relevance
“…Due to the difference of the charge between the emission sites and the nitrate ions, the most possible interactions between PVP and nitrate ions would be electrostatic interactions. Similar interactions have been proposed for the interactions between nitrates and polypyrrole [22], nitro-containing compounds with polymers [11,26,27]. In the presence of the same concentration of nitrate ions, especially at high concentrations, it was obviously observed that the C=O sites were more quenched than the N-C sites.…”
Section: Quenching Testssupporting
confidence: 72%
“…Due to the difference of the charge between the emission sites and the nitrate ions, the most possible interactions between PVP and nitrate ions would be electrostatic interactions. Similar interactions have been proposed for the interactions between nitrates and polypyrrole [22], nitro-containing compounds with polymers [11,26,27]. In the presence of the same concentration of nitrate ions, especially at high concentrations, it was obviously observed that the C=O sites were more quenched than the N-C sites.…”
Section: Quenching Testssupporting
confidence: 72%
“…Polymers can be intrinsically fluorescent due to an extended conjugated system Kang et al, 2007;Long et al, 2009;Samitsu et al, 2009;Xin et al, 2009;Zhang et al, 2007;Zhao et al, 2007;Zhu et al, 2009). A good example is that of poly(phenylene vinylene) (PPV) derivatives, which emit from blue to yellow-green.…”
Section: Polymer-based Nanofibersmentioning
confidence: 99%
“…Nitro-substituted groups such as 2,4-dinitrotoluene (DNT) and 2,4,6-trinitrotoluene (TNT) act as effective quenching analytes. Through the use of novel fluorophores [325] and conjugated polymers [326], rapid response dynamics of fluorescence quenched electrospun optical sensors can be utilized for detection of explosive compounds. Xue et al recently demonstrated an explosives detector based on a novel fluorophore that had a more favorable donor-acceptor interaction between itself and DNT compared with previous fluorophores.…”
Section: Other Applications Of Electrospun Fibers In Photonicsmentioning
confidence: 99%